Rethinking Student-Center Learning Approach in Indonesia's Islamic Higher Education Curriculum: A Systematic Literature Review - Kadafi, Muammar; Ulpah, Mariam (Badan Litbang dan Diklat Kementerian Agama RI, 2023)
When developing a curriculum for Islamic higher education, it is necessary to consider a student-centered learning and emphasize pedagogical principles in Islamic education. This study aims to find out what things need to be considered when designing the curriculum and how student-centered learning is implemented in Indonesia’s Islamic higher education curriculum. The method used is a systematic literature review. This study finds that the aspects that need to be considered in designing a student-centered approach in a curriculum that is in accordance with Islamic pedagogical principles include the storytelling pedagogical method, the method of the critical dialogue, the teacher's demonstration, homework assignments, reflection and inquiry discussion methods, the question-and-answer approach, and field studies. Meanwhile, theoretically, the curriculum applied in Indonesia is relevant to the aims of Islamic education in terms of components of the learning process and the outcomes of student-centered. However, there are still many obstacles to implementing the program